Dukungan Strategi Pembelajaran Dan Tingkat Sosial Ekonomi Orang Tua Terhadap Kemandirian Belajar Matematika Di Madrasah Aliyah Negeri Purwodadi - Werdiningsih, Endang, Prof. Dr. Sutama, M. Pd (2016)
The purpose of this study to analyze: 1) To examine the contribution of PBL learning strategy and DL contribute to learning independence matematika.2) To examine the contribution of their socio-economic level of parents relating to the independence of learning mathematics. 3) To examine the contribution of the interaction of socio-economic level of parents towards independent learning mathematics.This research is a quantitative research. This research was conducted in MAN Purwodadi in the academic year 2015/2016 with 32 respondents in class X IPA 1 as samples by random sampling technique. The technique of collecting data using questionnaires. Data were analyzed using, test the accuracy of the model, test, and classical assumption. Implementation of research results in the experimental class is done according to plan. That is, the teachers in implementing improvement is much better compared to when teachers perform validation ie from 72% to 84%. While the implementation of learning the control class can also be said to be either 80% of the maximum criteria. After knowing both normal and homogeneous class research the next step is testing the research hypothesis. For it is necessary to test the average difference of the two classes of research or by using the t test. After a thorough statistical test obtained t value 2.102. With df 56 on the real level of α = 0.05 is known t table of 2003. These results indicate that t is greater dari matematika dari t table. Therefore t coun t > t table (2.102> 2.003) and significance 0.040 < 0.05, then H0 is rejected.